Effect of sulphur on yield, nutrient uptake and economics of pearl millet (Pennisetum glaucum) and lentil (Lens culinaris) grown in sequence on an alluvial soil - SINGH, SANDEEP; SINGH, JAGPAL; KHAN, MOHAMMAD HALIM; PAL, ANIL KUMAR; KUMAR, SARVENDRA (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was carried out in kharif and rabi seasons of 2010-11 and 2011-12 at Panwari village of Agra district (Uttar Pradesh) to study the response of pearl millet (Pennisetum glaucum (L) R. Br. emend Stuntz) and lentil (Lens culinaris Medikus) grown in sequence to sulphur (0, 15, 30, 45 and 60 kg/ha) application on alluvial soil. The experiment was laid out in randomized block design with four replications. Results revealed that increasing levels of sulphur up to 30 kg S/ha significantly increased the plant height (224.7 cm), ear head length (29.1 cm), ear head diameter (10.85 cm), test weight (11.00 g) and grain weight/ear (33.95 g) as compared to control. Application of 30 kg S/ha increased significantly the mean grain and stover yield of pearl millet by 23.0 and 18.7% over control, respectively. The uptake of nutrients by pearl millet crop increased significantly due to sulphur application over control. The highest protein content (10.8%) and yield (351.0 kg/ha) of pearl millet grain was obtained with 60 and 30 kg S/ha, respectively. Sulphur application in preceding pearl millet crop at 45 kg S/ha was found to be best for growth and yield attributes of lentil. The residual S at 45 kg S/ha significantly increased the grain and straw yield of lentil by 0.47 and 0.65 t/ha over control, respectively. Such beneficial effect of S was also found in increasing uptake of nutrients and protein content (24.0%) and yield (474.3 kg/ha) of lentil. Application of 45 kg S/ha recorded the highest net returns of ` 63 922/ha, which was closely followed by 30 kg S/ha. The maximum value of benefit: cost ratio (3.78) in crop sequence was recorded with application of 45 kg S/ha. Agronomic efficiency and apparent S recovery were recorded higher at 30 kg S/ha in pearl millet and 45 kg S/ha in lentil. Application of 60 kg S/ha significantly improved the status of available S in post-harvest soil over initial value of sulphur.